1997
DOI: 10.1126/science.277.5326.684
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Language Analysis of Phonetic Units in Language Addressed to Infants

Abstract: In the early months of life, infants acquire information about the phonetic properties of their native language simply by listening to adults speak. The acoustic properties of phonetic units in language input to young infants in the United States, Russia, and Sweden were examined. In all three countries, mothers addressing their infants produced acoustically more extreme vowels than they did when addressing adults, resulting in a "stretching" of vowel space. The findings show that language input to infants pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

45
696
7
19

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 760 publications
(794 citation statements)
references
References 25 publications
45
696
7
19
Order By: Relevance
“…In addition, data reported by Bernstein Ratner (1984) show that the peripheral vowels, /i/, / /, /u/ and /ae/, are clarified in speech directed to pre-linguistic infants, such that these vowels are produced with little or no acoustic overlap with other vowels. Kuhl et al (1997) showed that the vowel space defined by /i/, / a/ and /u/ is expanded in speech directed to 6-month olds such that these corner vowels occur in a hyperarticulated form (other vowels were not analyzed); this was observed regardless of whether mothers were speaking English, Swedish or Russian. Presently, two months is the youngest age at which we have evidence for asymmetries in human vowel perception (Swoboda et al, 1978).…”
Section: Questions Raisedmentioning
confidence: 93%
“…In addition, data reported by Bernstein Ratner (1984) show that the peripheral vowels, /i/, / /, /u/ and /ae/, are clarified in speech directed to pre-linguistic infants, such that these vowels are produced with little or no acoustic overlap with other vowels. Kuhl et al (1997) showed that the vowel space defined by /i/, / a/ and /u/ is expanded in speech directed to 6-month olds such that these corner vowels occur in a hyperarticulated form (other vowels were not analyzed); this was observed regardless of whether mothers were speaking English, Swedish or Russian. Presently, two months is the youngest age at which we have evidence for asymmetries in human vowel perception (Swoboda et al, 1978).…”
Section: Questions Raisedmentioning
confidence: 93%
“…Language is one well-known example whereby the features of individual languages (e.g., phonemes) are accommodated within what appear to be inherent neural, perceptual, and cognitive constraints such that individuals develop the language to which they are exposed (R. Brown, 1973;Kuhl, 1994;Kuhl et al, 1997;Pinker, 1994). Aspects of this accommodation appear to involve the exoskeleton form of plasticity (e.g., for phoneme recognition) and occur as an experience-expectant feature of language development (Doupe & Kuhl, 1999).…”
Section: Development and Soft Modularitymentioning
confidence: 99%
“…It has been argued that the distinct phonetic categories in IDS serve to provide the infant with input that is optimized for learning certain aspects of the linguistic system (Kuhl et al 1997;de Boer and Kuhl 2003;Kirchhoff and Schimmel 2005). These hypotheses have in common a vision of IDS as an essentially listener-oriented speech style, in which the speaker expends additional effort in order to maximize the information content in the signal, making the infant listener's task easier.…”
Section: Devoicing In Idsmentioning
confidence: 99%
“…Research on IDS has shown that phonetic categories in IDS tend to be more distinct (Malsheen 1980;Masataka 1992;Andruski and Kuhl 1996;Kuhl et al 1997;Burnham et al 2002;Liu et al 2007;Cristià 2010) when compared to ADS. It has been argued that the distinct phonetic categories in IDS serve to provide the infant with input that is optimized for learning certain aspects of the linguistic system (Kuhl et al 1997;de Boer and Kuhl 2003;Kirchhoff and Schimmel 2005).…”
Section: Devoicing In Idsmentioning
confidence: 99%
See 1 more Smart Citation